2020
DOI: 10.1177/0306419019898824
|View full text |Cite
|
Sign up to set email alerts
|

Virtual reality and its role in improving student knowledge, self-efficacy, and attitude in the materials testing laboratory

Abstract: The aim of this work is to evaluate the efficacy of using virtual reality to develop training modules for students who are participating in mechanical engineering laboratory classes. We investigated the feasibility of applying virtual reality and augmented reality technologies in manufacturing and material testing training programs to increase academic achievement, engagement, attitudes and self-efficacy toward engineering and also in fostering more effective use of expensive lab-equipment. We hypothesized tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 11 publications
0
19
0
Order By: Relevance
“…The students also mentioned that the VL pump experiment is intuitive and consumes less time (Zhao et al, 2019). The work carried out at Texas A&M University, USA, shows that the female students spent more time in the VL tutorial (Srinivasa et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The students also mentioned that the VL pump experiment is intuitive and consumes less time (Zhao et al, 2019). The work carried out at Texas A&M University, USA, shows that the female students spent more time in the VL tutorial (Srinivasa et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…then D. [14]. Explaining that studying through virtual labs By combining e-learning, students become more interested about studying, which is backed by [25], who indicates that virtual reality-based online learning makes it easier for students to acquire learning information.…”
Section: Discussionmentioning
confidence: 99%
“…Although Joshi et al [52] demonstrated that gender influences affective factors, Sanchez-Sepulveda et al [105,107] demonstrated the inverse. Although Srinivasa et al [111] demonstrated that gender can affect learning gain, Joshi et al [52] showed the inverse. Beh et al [13] demonstrated that gender can affect usability.…”
Section: Individual Differences (Input Factor)mentioning
confidence: 99%